Coopetition as a Strategy to Improve the Global Ranking of Higher Education in Indonesia: SEM-PLS Approach - Hafidudin Hafidudin; Agus Rahayu; Syamsul Hadi Senen; Alfira Sofia (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Global university rankings such as QS World University Rankings and Times Higher Education (THE) have become the main benchmarks for assessing the competitiveness of higher education institutions at the international level. Although the number of Indonesian universities included in global rankings has increased, their ranking positions still lag behind those of other countries. This condition reflects the limited resources, the low level of sustainable international research collaboration, and the dominance of the paradigm of pure competition between institutions. On the other hand, empirical studies that integrate management and business perspectives, especially coopetition strategies, in the context of the global ranking of universities in Indonesia are still very limited. Objective: This study aims to analyze the influence of coopetition strategy on the global ranking performance of universities in Indonesia, with international research collaboration as a mediating variable.Methods: The study uses a quantitative approach through a survey of 120 respondents representing public and private universities in Indonesia who are included in the QS and/or THE rankings. The data was analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the help of SmartPLS software. Results: The results of the analysis showed that coopetition had a positive and significant effect on international research collaboration (β = 0.65; p < 0.001) and on global ranking performance (β = 0.31; p < 0.01). International research collaborations have also been shown to have a significant effect on global ranking performance (β = 0.46; p < 0.001) and act as a partial mediator in the relationship between coopetition and global ranking performance (indirect β = 0.30; p < 0.001). The value of the determination coefficient shows that the model is able to explain 57% of the variation in global ranking performance. Conclusion: These findings confirm that the coopetition strategy is an effective management and business approach to strengthen the global competitiveness of Indonesian universities.